Screening of aqueous extract of fenugreek seeds for its anti-inflammatory potential in albino rats - Brahadeesh Mayathevar (Asian Journal of Medical Sciences, 2022)
Background: Inflammation is a common defense mechanism that involves a complicated network of cell-cell, cell-mediator, and tissue interaction. Fenugreek (Trigonella foenumgraecum L.) seeds are used for the treatment of many inflammatory conditions. Aims and Objectives: The aim of the study was to analyze the anti-inflammatory properties of aqueous extracts of fenugreek seeds in albino rats and compare it to control and standard anti-inflammatory treatments in animal models of acute and chronic inflammation. Materials and Methods: The methods employed to study the anti-inflammatory activity are carrageenan-induced rat paw edema and turpentine induced arthritis model in rats for acute inflammatory model and cotton wool pellet granuloma in rats for chronic inflammatory model following acquisition of the Institutional Ethics Committee approval. The control group was given 1% gum acacia, standard group was given 10 mg/kg Indomethacin dissolved in distilled water and test group was given 200 mg/kg of aqueous extract of fenugreek seeds suspended in 1% gum acacia orally. Results: The test group displayed almost equal increase in paw volume edema as that of the standard group under experimental conditions. In Carrageenan-induced rat paw edema model and turpentine induced arthritis model, aqueous extract of fenugreek seeds and indomethacin had comparable anti-inflammatory effect. The anti-granuloma effect of aqueous extract of fenugreek seeds was of moderate degree compared to the standard under the present experimental conditions. Conclusion: When compared to standard indomethacin, the aqueous extract of fenugreek seeds demonstrated significant anti-inflammatory activity in acute models of inflammation and moderate activity in chronic models of inflammation.